Analisis Kesulitas Siswa Sekolah Dasar dalam Menyesesaikan Soal Statistika - Nurjanah, Alya Rifa; Hartanti, ⁠Riska; Susanti, Desi; Ayuningsih, Tinaningrum; Murtiyasa, Budi; Setyaningsih, Nining (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The study aims to identify the forms of students’ learning difficulties and the factors underlying them. This research employed a descriptive qualitative method involving seven sixth-grade students at SDN Tegalharjo, Surakarta. Data were collected through semi-structured interviews, classroom observations, and document analysis, and then analyzed using the Miles and Huberman model. The results indicate that most students have a good understanding of basic statistical concepts due to the contextual learning approach applied by the teacher; however, the main difficulties arise at the calculation stage, particularly in calculating the mean with decimal results and determining the median due to a lack of accuracy in ordering data. The factors contributing to these difficulties include limited arithmetic skills, low accuracy, and varying levels of learning support from families. Students’ learning motivation is relatively high, especially when the material is linked to real-life experiences and practical activities. These findings emphasize the need to strengthen basic numeracy skills, improve accuracy, and involve the learning environment to enhance elementary school students’ understanding of Statistics. Based on these findings, it can be concluded that improving elementary students’ understanding of Statistics should focus on reinforcing basic numeracy skills, accuracy in calculation processes, and synergy between contextual learning strategies and learning environment support. Keyword: Mathematics, Elementary School, Statistics.